Effect of microbial transglutaminase (Streptomyces mobaraensis) on the restructuring of cooked tuna (Thunnus albacares) fragments - Mieles Quiñónez, Josselyn Nicole (2026)
Industrial fish processing, especially tuna, generates large volumes of by-products such as meat fragments which, despite their high nutritional value, present technological limitations for optimal utilization. This study evaluated the use of microbial transglutaminase as a restructuring agent to improve the functional properties of the cooked tuna fragments. The effect of different enzyme concentrations (0.5 % and 1.0 %) on the physicochemical properties of restructured tuna fragments was analyzed over a 7-day period of refrigerated storage. The experimental design included four treatments (Control without fragmentation, fragments without enzyme, and fragments treated with 0.5 % and 1.0 % TG). Analyses included texture profile, instrumental color stability, and liquid retention capacity. The results demonstrated substantial improvements in multiple functional properties. In textural terms, the enzyme significantly increased hardness, cohesiveness, and gumminess compared to untreated fragments. Simultaneously, water and oil retention capacity showed progressive increases with enzyme concentration, reaching maximum values with the 1.0 % treatment (88.87 +- 0.01 % for water and 87.13 +- 0.01 % for oil). Additionally, transglutaminase reduced chromatic alterations associated with muscle tissue fragmentation, preserving visual stability during storage. The 0.5 % concentration was identified as the most optimal, providing significant improvements in all evaluated properties, while higher concentrations offered marginal benefits. These findings establish a solid technological basis for development of restructured products, confirming the effectiveness of microbial transglutaminase.